Development of a Clioquinol Nanocarrier as a New, Promising Option for the Treatment of Dermatomycosis - Simone Jacobus Berlitz; Paula Reginatto; Gabriella da Rosa Monte Machado; Alexandre Meneghello Fuentefria; Fernando Dal Pont Morisso; Renata Vidor Contri; Irene Clemes Külkamp-Guerreiro (MDPI AG, 2023)
Dermatomycosis is a common fungal infection, and its treatment is limited by few antifungal agents. Clioquinol (CQ) is an antiparasitic agent that has been studied for new uses, such as antifungal and antiviral applications. CQ was incorporated into a lipid-based nanocarrier as a new, promising option for dermatomycosis. This study aimed to develop a CQ-loaded lipid-based nanocarrier for cutaneous application and to evaluate its antifungal activity. CQ-loaded nanoformulation (LBN-CQ) was developed using the ultrasonication method, and the particle size, polydispersity index (PDI), pH, zeta potential, and drug content were monitored for 45 days. To evaluate antifungal activity, broth microdilution and a time-kill assay were performed. LBN-CQ presented a particle size of 91 ± 3 nm and PDI of 0.102 ± 0.009. The zeta potential and pH values were −9.7 ± 2.0 mV and 6.0 ± 0.1, respectively. The drug content was 96.4 ± 2.3%, and the encapsulation efficiency was 98.4%. LBN-CQ was able to reduce the minimum inhibitory concentration (MIC) in a 2-fold or 4-fold manner in most of the tested strains. Additionally, LBN-CQ presented stable fungistatic action that was not concentration- or time-dependent. In conclusion, the developed CQ-loaded nanocarrier is a promising treatment for skin fungal infections and a promising candidate for future randomized clinical trials.